A gateway towards a sustainable environment in emerging countries: the nexus between green energy and human Capital. Issue 1 (31st December 2022) - Huang, Shi-Zheng; Chien, Fengsheng; Sadiq, Muhammad
Abstract: The nexus between economic growth (EG) and carbon emission has been examined extensively, specifically in consumption-based CO2 . However, the role of human capital, green energy, and sustainable economic growth in determining the carbon emission is yet to be explored specifically from emerging economies. This study aimed to examine the impact of human capital index, green energy, EG in terms of GDP, and square of GDP on carbon emission for long-short run with the help of CS-ARDL. The data for study variables was collected from 1995 to 2018. The study findings confirmed that there exists CSD, cointegration, and slope heterogeneity among the study variables. In contrast, the output through CS-ARDL indicated that the main reason for higher carbon emission in the targeted economies are economic growth under long-short run estimation. Additionally, the role of green energy and human capital index is also constructive in lowering the environmental degradation for both long-run and short-run estimation. Finally, some policy implications are also convassed at the end of the research.